The Aggressive Behaviour in Elementary School and Factors Can Be Influence (Journal of Primary Education, 2019)
The study aims to identify forms of aggressive behavior which are usually displayed by elementary students and analyze the influence of peer interaction, school discipline and authoritarian parenting on the aggressiveness of elementary school students in 4th and 5th grade at Elementary School 2 Bacin and Elementary School 3 Bacin Kudus. Quantitative research uses experimental research methods and comparative causal approaches. The sample selection uses purposive sampling technique. The sample characteristics used were students of grade IV-V Elementary School 2 Bacin and Elementary School 3 Bacin Kudus, based on screening raised by authoritarian parenting. Data collection uses observation and questionnaire scale. Data analysis using multiple linear regression with the help of SPPSS 21 for Windows. Based on the results of the study, the most common form of aggressiveness is physical aggression in the form of fights between students that trigger violence. The results of the study also showed that there was a significant influence among peer interaction, school discipline and authoritarian parenting on aggressive behavior simultaneously (Fvalue = 3.920 > from Ftable = 2.81). The results of partial hypothesis testing showed that peer interaction and authoritarian parenting had a positive but not significant effect on students' aggressive behavior. School discipline has a negative and significant effect on students' aggressive behavior. Peer interactions, school discipline, and authoritarian parenting explain aggressive behavior by 20.4 %, while 79.6% are influenced by other factors such as ethological, sociological, genetic, situational influences and media violence.